Cellular apoptosis of HFF cells by inorganic nanoparticles not susceptible to modulation by Toxoplasma gondii infection in vitro. (February 2019) - Adeyemi, Oluyomi Stephen; Otohinoyi, David Adeiza; Awakan, Oluwakemi Josephine; Adeyanju, Adebukola Anne
Abstract: The interaction of nanoparticles with living cells is becoming one of the urgent areas of collaborative research in materials science and biology. Previously, we showed that nanoparticles have promising anti- Toxoplasma gondii properties. Meanwhile, Toxoplasma gondii has been shown to avert apoptosis in host cells whereas nanoparticles have been implicated for apoptotic tendency. Therefore, in the present study, we assessed the in vitro apoptotic properties of inorganic nanoparticles in the absence or presence of Toxoplasma infection and/or small molecules used as metabolic modulators. Results showed that inorganic nanoparticles dose-dependently caused cellular apoptosis. However, in the presence of infection by Toxoplasma gondii, nanoparticles-induced cellular apoptosis was not mitigated. Likewise, use of several small molecules (anti-metabolites) as metabolic modulators either mildly or nearly failed to abate cellular apoptosis by nanoparticles. Taken together, our findings do not only confirm the apoptotic potential of inorganic nanoparticles but show evidence that cellular apoptosis by inorganic nanoparticles of gold and silver might not be susceptible to modulation by Toxoplasma gondii infection. The findings are new and contribute to deepen our understanding of the cellular interaction of nanoparticles. Highlights: Gold and silver nanoparticles caused apoptosis in HFF cells Apoptosis of HFF cells by nanoparticles not modulated by Toxoplasma infection Small molecules (metabolic modulators) mildly averted apoptosis of HFF cells by nanoparticles